Knowledge of pregnant women about anemia is related with adherence to iron tablets - Baksono Winardi; Elga Caecaria Grahardika Andani (Majalah Obstetri dan Ginekologi, 2018)
Objectives: to identify association between knowledge of pregnant women about anemia and the adherence to consume iron tablets in BPM Titik Suharti, Surabaya, IndonesiaMaterials and Methods: Observational analysis cross sectional study. Population consisted of 55 trimester pregnant women in BPM Titik Suharti, Surabaya, in March-April 2017. Samples were recruited using consecutive sampling. The number of sample was 35 respondents. Data were analyzed using chi-square test.Results: This research showed that all of the less knowledgeable women on anemia (100.00%) were non-adherent to consume iron tablets, almost all moderately knowledgeable women (92.9%) were adherent, and all of the fully knowledgeable women (100.00%) were adherent. Fisher exact test in significance level of 0.05 revealed p value equal to 0.0001, indicating association between knowledge about anemia and adherence to consume iron tablets at BPM Titik Suharti, Surabaya, Indonesia.Conclusion: There is an association between knowledge of pregnant women about anemia with adherence to iron tablets.